The oral microbiome diversity and its relation to human diseases - He, Jinzhi; Li, Yan; Cao, Yangpei; Xue, Jin; Zhou, Xuedong (Folia microbiologica, 2015)
As one of the most clinically relevant human habitats, the human mouth is colonized by a set of microorganisms, including bacteria, archaea, fungi, and viruses. Increasing evidence has supported that these microbiota contribute to the two commonest oral diseases of man (dental caries and periodontal diseases), presenting significant risk factors to human health conditions, such as tumor, diabetes mellitus, cardiovascular diseases, bacteremia, preterm birth, and low birth weight in infants. It is widely accepted that oral microorganisms cause diseases mainly by a synergistic or cooperative way, and the interspecies interactions within the oral community play a crucial role in determining whether oral microbiota elicit diseases or not. Since a comprehensive understanding of the complex interspecies interactions within a community needs the knowledge of its endogenous residents, a plenty of research have been carried out to explore the oral microbial diversity. In this review, we focus on the recent progress in this field, including the oral microbiome composition and its association with human diseases.
Keywords: mikrobiota; ústa; nemoci úst; Bacteria; Animals; Humans; Microbiota; Mouth Diseases; biodiverzita; lidé; zvířata; Mouth; Biodiversity